An upper bound for the regularity of powers of edge ideals - Herzog, Jürgen; Hibi, Takayuki (MATHEMATICA SCANDINAVICA, 2020)
For a finite simple graph G we give an upper bound for the regularity of the powers of the edge ideal I(G).